Strengthening Sustainability Literacy Through an International Guest Lecture on Environmental, Social, and Governance (ESG) - Harfiahani Indah Rakhma Ningtyas; Ufi Rumefi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This study aims to describe the implementation of an international guest lecture on Environmental, Social, and Governance (ESG) and examine its role in enhancing students’ understanding of sustainability issues in business and management education. Methodology: This study employed a descriptive, qualitative approach. This activity was conducted through an academic collaboration between the Yadika Institute of Technology and Business Pasuruan, Indonesia, and Management and Science University (MSU), Malaysia. The lecture was delivered by undergraduate students from the Faculty of Business Management and Accounting. Data were collected through observation, documentation of the activity, and student feedback, and were analyzed using descriptive analyses. Results: The findings indicate that the international guest lecture contributed to increasing students’ awareness and understanding of Environmental and Social Framework (ESF) concepts and sustainability practices. Students actively participated in the lecture and discussion sessions, demonstrating a strong interest in topics related to responsible business practices and global sustainability challenges.   Conclusions: This study concludes that international guest lectures can serve as an effective educational platform for introducing ESG awareness and strengthening sustainability education in higher education institutions.   Limitations: This study is limited to a single guest lecture activity involving students from one institution and relies primarily on descriptive analyses. As such, funding should be interpreted with caution and may not be generalizable to other institutional settings. Contributions: This study contributes to sustainability education by highlighting the role of international academic collaboration in enhancing ESG literacy among students in the business and management disciplines.